A saúde e a condição de trabalho do professor/profissional de educação física: estado da arte nos periódicos nacionais - SILVA, Nayara Reis da (2022)
The present study analyzed the health and work theme of the Physical Education teacher / professional, based on a literature review study, of the type of state of the art, which systematized the academic production of the subject in question in the national journals in the area, in the 2000 to 2020. We identified 4 articles in 56 magazines and evidence that the written production on the theme is minimal. In general, the articles denounce that effects the effects of precariousness of work are the following pathologies: Pain in the lumbar region, indicating musculoskeletal disorders, flu, inflammation of the skin, eyes, skin cancer, prevalence of Osteomuscular Disorder Syndrome; and Burnout Syndrome. It was also found that the working conditions of Physical Education agents are precarious fields, resulting in the illness of these professionals.